Antistatic fluoroplastic for pipe lining and method for its production
Patent Information
- Application Number
- CN202611050883.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]其二,力学强度不足,为弥补这一短板,现有技术尝试引入玻璃纤维、碳纤维等增强相,但纤维与氟塑料基体之间极差的界面相容性往往导致增强效果不及预期,而金属骨架复合则存在工艺复杂、成本较高的局限
本发明通过结构设计,在碳纳米管表面包覆大分子改性试剂,制得碳纳米管抗静电改性料,作为添加剂,大分子改性试剂链段与氟塑料基体之间的“氟-氟亲和”相互作用,显著降低了碳纳米管与氟塑料之间的界面张力,有效避免了常规无机填料因表面能差异过大而出现的严重团聚现象,实现了改性剂在氟塑料基体中的均匀分散。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of plastics technology, specifically to an antistatic fluoroplastic for pipe linings and its production method. Background Technology
[0002] Fluoroplastics are widely used as anti-corrosion lining materials for metal pipelines due to their excellent chemical corrosion resistance, low coefficient of friction, and wide temperature range stability, and are applied in the transportation of highly corrosive media in petrochemical, pharmaceutical, and fine chemical industries. However, with increasingly demanding operating conditions for industrial pipeline systems and continuously improving safety standards, existing fluoroplastic pipeline lining technology faces significant challenges in two aspects.
[0003] Firstly, there is the risk of static electricity buildup. Fluoroplastics are excellent electrical insulators, but when transporting low-conductivity media such as hydrocarbon solvents and organic liquids, the friction between the fluid and the inner wall easily generates static charge. If this static charge cannot be effectively dissipated, it can accumulate to a critical value, potentially triggering a spark discharge and causing flammable or explosive media to ignite or even explode. Current technologies achieve antistatic properties by adding fillers such as conductive carbon black and graphene to the fluoroplastic matrix, but high filler content often compromises the material's mechanical properties and processability. Another approach uses a multi-layer composite structure, with conductive layers to conduct static electricity to the external metal pipe; however, the interlayer bonding strength and long-term service reliability still need improvement.
[0004] Secondly, the mechanical strength is insufficient. To compensate for this shortcoming, existing technologies have attempted to introduce reinforcing phases such as glass fiber and carbon fiber. However, the extremely poor interfacial compatibility between the fiber and the fluoroplastic matrix often leads to the reinforcement effect being less than expected. Meanwhile, metal skeleton composites have limitations such as complex processes and high costs.
[0005] Therefore, developing a fluoroplastic pipe lining material with both high-efficiency antistatic properties and excellent mechanical strength, and its preparation method, has significant engineering application value and is urgently needed by the market. Summary of the Invention
[0006] In order to solve the problems mentioned in the background art, the purpose of this invention is to provide an antistatic fluoroplastic for pipe lining and a method for producing the same.
[0007] The objective of this invention can be achieved through the following technical solutions: An antistatic fluoroplastic for pipe lining, the formulation comprising, by weight parts, the following raw materials: Ethylene-tetrafluoroethylene copolymer: 92-100 parts; Carbon nanotube antistatic modifier: 4.5-8.4 parts; Filler: 5-12 parts; Antioxidant: 0.5-1.5 parts; Lubricant: 1-3 parts; The carbon nanotube antistatic modified material is a carbon nanotube with a surface coated with a macromolecular modifying agent.
[0008] As a further aspect of the present invention, the carbon nanotube antistatic modified material is prepared by the following method: Step 1: Add carbon nanotubes to a mixed solution of concentrated hydrochloric acid and concentrated nitric acid, disperse evenly, turn on the heater, maintain the temperature at 60-70℃, and continue stirring for 3-5 hours. Cool down and discharge the material, wash until neutral, and then vacuum dry to obtain acidified carbon nanotubes. In the above technical solution, concentrated hydrochloric acid and concentrated nitric acid are used to acidify carbon nanotubes, which can generate oxygen-containing functional groups such as hydroxyl and carboxyl groups on their surface, thus producing acidified carbon nanotubes.
[0009] Step 2: Add acidified carbon nanotubes to deionized water and disperse evenly to prepare a dispersion with a mass fraction of 10-15%. Add macromolecular modifying reagent to N,N-dimethylformamide to prepare a modified solution with a mass fraction of 5-10%. Then, slowly add the modified solution dropwise to the dispersion at a stirring rate of 300-500 rpm. After the addition is complete, adjust the pH to 7.5-8.5, continue stirring at room temperature for 6-9 hours, filter to separate the solid material, wash and vacuum dry to obtain the antistatic modified carbon nanotube material.
[0010] Since the carboxyl groups of acidified carbon nanotubes carry a negative charge in aqueous solution, they can undergo electrostatic self-assembly with macromolecular modifying agents carrying quaternary ammonium cations. This allows the macromolecular modifying agents to coat the surface of carbon nanotubes, thereby achieving coating modification of carbon nanotubes and producing antistatic modified carbon nanotube materials.
[0011] As a further aspect of the present invention, the volume ratio of concentrated hydrochloric acid to concentrated nitric acid is 1:1.
[0012] As a further aspect of the present invention, the macromolecular modifying agent is prepared by the following method: Anhydride monomer, glycidyltrimethylammonium chloride, and organic solvent were added to a polymerization reactor, and nitrogen gas was introduced for protection. Then, stirring was started, and after the mixture was homogeneous, catalyst was added and stirred until homogeneous. After the addition was complete, heating was started, and the polymerization reaction was carried out under heat and stirring. After the reaction was completed, the product was precipitated, filtered, and vacuum dried to obtain a macromolecular modified reagent.
[0013] It should be noted that the macromolecular modifying agent is prepared by using acid anhydride monomers and glycidyltrimethylammonium chloride as raw materials, which undergo ring-opening polymerization under the action of a catalyst to obtain a macromolecular modifying agent containing fluorine segments and quaternary ammonium cationic segments in its structure.
[0014] As a further aspect of the present invention, the anhydride monomer is any one of 4-fluorophthalic anhydride, 4,5-difluorophthalic anhydride, or hexafluoroglutaric anhydride.
[0015] As a further aspect of the present invention, the molar ratio of the acid anhydride monomer and glycidyltrimethylammonium chloride is 1:1-1.2.
[0016] As a further aspect of the present invention, the catalyst is a bimetallic DMC catalyst.
[0017] As a further aspect of the present invention, the polymerization reaction is carried out at a temperature of 90-100°C for a time of 12-18 hours.
[0018] As a further aspect of the present invention, the solvent for the polymerization reaction is a mixed solution of ethyl acetate and toluene in a volume ratio of 1:1.
[0019] A method for producing antistatic fluoroplastics for pipe linings includes the following steps: Step 1: Add ethylene-tetrafluoroethylene copolymer, carbon nanotube antistatic modifier, filler, antioxidant and lubricant to a high-speed mixer according to the formula, and mechanically stir to mix evenly to form a premix. The second step is to feed the premixed material into an extruder for melt extrusion granulation to obtain the finished fluoroplastic.
[0020] The beneficial effects of this invention are: This invention utilizes structural design to coat the surface of carbon nanotubes with macromolecular modifying agents, thereby preparing an antistatic modified carbon nanotube material as an additive. The "fluorine-fluorine affinity" interaction between the macromolecular modifying agent chain segments and the fluoroplastic matrix significantly reduces the interfacial tension between the carbon nanotubes and the fluoroplastics, effectively avoiding the severe agglomeration phenomenon that occurs in conventional inorganic fillers due to excessive surface energy differences, and achieving uniform dispersion of the modifier in the fluoroplastic matrix.
[0021] On the one hand, uniformly dispersed carbon nanotubes can generate stable conductive pathways, but the dispersed carbon nanotubes cannot directly contact each other, resulting in discontinuous conductive pathways. On the other hand, macromolecular modified reagent segments have a certain ionic conductivity, and different molecular chains can contact each other, which is conducive to building a network of continuous electrostatic dissipation channels and improving the antistatic effect of the material.
[0022] On the other hand, carbon nanotubes can serve as a reinforcing core. With their ultra-high aspect ratio and specific surface area, combined with the efficient stress transfer achieved by excellent interfacial compatibility, they can significantly improve the mechanical strength of the material and overcome the shortcomings of insufficient mechanical strength of fluoroplastics.
[0023] Of course, any product implementing this invention does not necessarily need to achieve all of the advantages described above at the same time. Detailed Implementation
[0024] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] Example 1 An antistatic fluoroplastic for pipe lining, the formulation comprising, by weight parts, the following raw materials: Ethylene-tetrafluoroethylene copolymer: 92 parts; Carbon nanotube antistatic modifier: 4.5 parts; Calcium carbonate: 5 parts; Antioxidant 1010: 0.5 parts; Calcium stearate: 1 part; The method for preparing the antistatic fluoroplastic includes the following steps: Step 1: Add ethylene-tetrafluoroethylene copolymer, carbon nanotube antistatic modifier, calcium carbonate, antioxidant 1010 and calcium stearate to a high-speed mixer according to the formula amount, and mechanically stir to mix evenly to form a premix. The second step is to feed the premixed material into an extruder for melt extrusion granulation to obtain the finished fluoroplastic.
[0026] The carbon nanotube antistatic modified material was prepared using the following method: Step A: Add 1.5g of carbon nanotubes to a mixed solution of 50mL concentrated hydrochloric acid and 50mL concentrated nitric acid. After dispersing evenly, turn on the heating and maintain the temperature at 70℃. Continue stirring for 4 hours, cool down and discharge the material, wash until neutral, and then vacuum dry to obtain acidified carbon nanotubes. Step B: Add 0.6g of 4,5-difluorophthalic anhydride, 0.5g of glycidyltrimethylammonium chloride, and a 1:1 volume ratio of ethyl acetate and toluene to the polymerization reactor. Purge with nitrogen for protection, then start stirring. After mixing evenly, add 0.01g of bimetallic DMC catalyst and stir until homogeneous. After the addition is complete, start heating and maintain the temperature at 100℃ for stirring and polymerization for 16h. After the reaction is complete, precipitate, filter, and vacuum dry to obtain the macromolecular modified reagent. Step C: Add acidified carbon nanotubes to deionized water and disperse evenly to prepare a dispersion with a mass fraction of 10%; add macromolecular modifying reagent to N,N-dimethylformamide to prepare a modified solution with a mass fraction of 5%; then, under a stirring speed of 300 rpm, slowly add 10 mL of the modified solution to 20 mL of the dispersion. After the addition is complete, adjust the pH to 8, continue stirring at room temperature for 8 hours, filter to separate the solid material, wash and vacuum dry to obtain the antistatic modified carbon nanotube material.
[0027] Example 2 An antistatic fluoroplastic for pipe lining, the formulation comprising, by weight parts, the following raw materials: Ethylene-tetrafluoroethylene copolymer: 95 parts; Carbon nanotube antistatic modifier: 7.5 parts; Calcium carbonate: 8 parts; Antioxidant 1010: 1 part; Calcium stearate: 2 parts; The method for preparing the antistatic fluoroplastic includes the following steps: Step 1: Add ethylene-tetrafluoroethylene copolymer, carbon nanotube antistatic modifier, calcium carbonate, antioxidant 1010 and calcium stearate to a high-speed mixer according to the formula amount, and mechanically stir to mix evenly to form a premix. The second step is to feed the premixed material into an extruder for melt extrusion granulation to obtain the finished fluoroplastic.
[0028] The preparation method of the carbon nanotube antistatic modified material is the same as that in Example 1.
[0029] Example 3 An antistatic fluoroplastic for pipe lining, the formulation comprising, by weight parts, the following raw materials: Ethylene-tetrafluoroethylene copolymer: 100 parts; Carbon nanotube antistatic modifier: 8.4 parts; Calcium carbonate: 12 parts; Antioxidant 1010: 1.5 parts; Calcium stearate: 3 parts; The method for preparing the antistatic fluoroplastic includes the following steps: Step 1: Add ethylene-tetrafluoroethylene copolymer, carbon nanotube antistatic modifier, calcium carbonate, antioxidant 1010 and calcium stearate to a high-speed mixer according to the formula amount, and mechanically stir to mix evenly to form a premix. The second step is to feed the premixed material into an extruder for melt extrusion granulation to obtain the finished fluoroplastic.
[0030] The preparation method of the carbon nanotube antistatic modified material is the same as that in Example 1.
[0031] Comparative Example 1 An antistatic fluoroplastic for pipe lining differs from Example 2 in that the carbon nanotube antistatic modifier is replaced with a mixture of acidified carbon nanotubes and macromolecular modifier in a mass ratio of 1:4, while all other aspects remain the same.
[0032] The preparation methods of the acidified carbon nanotubes and macromolecular modifiers are described in Example 1.
[0033] Comparative Example 2 An antistatic fluoroplastic for pipe lining differs from Example 2 in that the carbon nanotube antistatic modified material is replaced with acidified carbon nanotubes, while the rest are the same.
[0034] Comparative Example 3 An antistatic fluoroplastic for pipe lining differs from Example 2 in that the carbon nanotube antistatic modifier is replaced with a macromolecular modifier, while the rest are the same.
[0035] The preparation method of the macromolecular modifier is described in Example 1.
[0036] Comparative Example 4 An antistatic fluoroplastic for pipe lining differs from Example 2 in that the carbon nanotube antistatic modifier is removed, while the rest are the same.
[0037] Test case The fluoroplastics used in the examples and comparative examples were made into various test strips that met the specifications, and various performance tests were conducted. The results are recorded in Table 1:
[0038] Tensile properties were tested according to standard GB / T 1040.1-2025, with a tensile rate of 100 mm / min. Resistivity testing was performed according to standard GB / T 1410-2006: Analysis and testing results show that fluoroplastics made with carbon nanotube antistatic modifiers exhibit good mechanical strength and antistatic properties. However, directly adding a mixture of acidified carbon nanotubes and macromolecular modifiers results in a simultaneous decline in mechanical and antistatic properties due to the dispersibility issues of the acidified carbon nanotubes, which prevent them from effectively exerting their reinforcing effect and forming stable conductive pathways. Using acidified carbon nanotubes directly as an additive also suffers from dispersibility problems and loses the synergistic conductive effect of the macromolecular modifier, further reducing the antistatic properties of the fluoroplastics. Finally, directly using macromolecular modifiers as additives fails to utilize the reinforcing and conductive advantages of carbon nanotubes, leading to a significant decrease in the various properties of the fluoroplastics.
[0039] This document uses specific examples to illustrate the principles and implementation methods of the present invention. The descriptions of these embodiments are merely to aid in understanding the method and core ideas of the present invention, including the best mode, and to enable any person skilled in the art to practice the present invention, including manufacturing and using any device or system, and implementing any combined method. It should be noted that those skilled in the art can make various improvements and modifications to the present invention without departing from its principles, and these improvements and modifications also fall within the scope of protection of the claims. The scope of protection of this patent is defined by the claims and may include other embodiments that can be conceived by those skilled in the art. If these other embodiments have structural elements similar to those expressed in the claims, or if they include equivalent structural elements that are not substantially different from those expressed in the claims, then these other embodiments should also be included within the scope of the claims.
Claims
1. An antistatic fluoroplastic for pipe lining, characterized in that, The formula is measured by parts by weight and includes the following ingredients: Ethylene-tetrafluoroethylene copolymer: 92-100 parts; Carbon nanotube antistatic modifier: 4.5-8.4 parts; Filler: 5-12 parts; Antioxidant: 0.5-1.5 parts; Lubricant: 1-3 parts; The carbon nanotube antistatic modified material is a carbon nanotube with a surface coated with a macromolecular modifying agent.
2. The antistatic fluoroplastic for pipe lining according to claim 1, characterized in that, The carbon nanotube antistatic modified material is prepared by the following method: Step 1: Add carbon nanotubes to a mixed solution of concentrated hydrochloric acid and concentrated nitric acid for acidification treatment to obtain acidified carbon nanotubes. Step 2: Use macromolecular modifying reagents as electrostatic self-assembly reagents to coat and modify acidified carbon nanotubes to obtain antistatic modified carbon nanotubes.
3. The antistatic fluoroplastic for pipe lining according to claim 2, characterized in that, The volume ratio of concentrated hydrochloric acid to concentrated nitric acid is 1:
1.
4. The antistatic fluoroplastic for pipe lining according to claim 2, characterized in that, The macromolecular modifying agent is prepared by polymerization reaction using acid anhydride monomers and glycidyltrimethylammonium chloride as raw materials under the action of a catalyst.
5. The antistatic fluoroplastic for pipe lining according to claim 4, characterized in that, The anhydride monomer is any one of 4-fluorophthalic anhydride, 4,5-difluorophthalic anhydride, or hexafluoroglutaric anhydride.
6. The antistatic fluoroplastic for pipe lining according to claim 4, characterized in that, The molar ratio of the acid anhydride monomer and glycidyltrimethylammonium chloride is 1:1-1.
2.
7. The antistatic fluoroplastic for pipe lining according to claim 4, characterized in that, The catalyst is a bimetallic DMC catalyst.
8. The antistatic fluoroplastic for pipe lining according to claim 4, characterized in that, The polymerization reaction is carried out at a temperature of 90-100℃ for 12-18 hours.
9. The antistatic fluoroplastic for pipe lining according to claim 4, characterized in that, The solvent for the polymerization reaction is a mixed solution of ethyl acetate and toluene in a volume ratio of 1:
1.
10. A method for producing antistatic fluoroplastics for pipe linings as described in claim 1, characterized in that, Includes the following steps: Step 1: Add ethylene-tetrafluoroethylene copolymer, carbon nanotube antistatic modifier, filler, antioxidant and lubricant to a high-speed mixer according to the formula, and mechanically stir to mix evenly to form a premix. The second step is to feed the premixed material into an extruder for melt extrusion granulation to obtain the finished fluoroplastic.